2015
DOI: 10.2196/jmir.4378
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Direct-to-Consumer Genetic Testing: A Systematic Review

Abstract: BackgroundDirect-to-consumer genetic tests (DTC-GT) are easily purchased through the Internet, independent of a physician referral or approval for testing, allowing the retrieval of genetic information outside the clinical context. There is a broad debate about the testing validity, their impact on individuals, and what people know and perceive about them.ObjectiveThe aim of this review was to collect evidence on DTC-GT from a comprehensive perspective that unravels the complexity of the phenomenon.MethodsA sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 132 publications
(395 reference statements)
0
82
0
5
Order By: Relevance
“…The reviews summarized below were picked to represent a range of types of genetic and genomic testing, each of which could generate a distinct psychosocial response among recipients. The topics include the psychosocial impact of Huntington disease testing, the decision to decline testing, testing for hereditary cancers, testing of symptomatic individuals, carrier testing, direct‐to‐consumer testing, pediatric testing, and familial communication of risks . After presenting these examples, I will synthesize the systematic review findings, discuss the quality of the source literature, and summarize overarching gaps and recommendations identified by the reviews.…”
Section: Relevance Of Systematic Reviewsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reviews summarized below were picked to represent a range of types of genetic and genomic testing, each of which could generate a distinct psychosocial response among recipients. The topics include the psychosocial impact of Huntington disease testing, the decision to decline testing, testing for hereditary cancers, testing of symptomatic individuals, carrier testing, direct‐to‐consumer testing, pediatric testing, and familial communication of risks . After presenting these examples, I will synthesize the systematic review findings, discuss the quality of the source literature, and summarize overarching gaps and recommendations identified by the reviews.…”
Section: Relevance Of Systematic Reviewsmentioning
confidence: 99%
“…A systematic review by Loredana Covolo et al aimed to clarify the impacts of DTC genetic and genomic testing, partly by describing how recipients respond to learning about their risks . The review identified thirty‐seven studies addressing the impact of DTC testing on consumers, but the focus here will be on the nine research studies that explored the perspectives of individuals who actually received test results.…”
Section: Psychosocial Impact Of Direct‐to‐consumer Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Proponents argue that they empower consumers to take responsibility for their health 24 and improve the quality of their life 25 . However, researchers and health professionals have raised concerns about the clinical validity of DTC genetic tests, particularly in relation to susceptibility testing for complex disease, such as diabetes or dementia 26, 27 . Specifically, researchers have argued that these tests fail to take into account non-genetic factors that can contribute to complex disease 24 .…”
Section: Introductionmentioning
confidence: 99%